Coupling Sap Flow Velocity and Amino Acid Concentrations as an Alternative Method to 15N Labeling for Quantifying Nitrogen Remobilization by Walnut Trees - Ela Frak; Millard, Peter; Le Roux, Xavier; Sabine Guillaumie; Wendler, Renate (Plant physiology (Bethesda), 2002)
The temporal dynamics of N remobilization was studied in walnut (Juglans nigra × regia) trees growing in sand culture. Trees were fed with labeled N (15N) during 1999 and unlabeled N in 2000. Total N and 15N contents in different tree compartments were measured during 80 d after bud burst and were used to estimate N remobilization for spring growth. The seasonal (and occasionally diurnal) dynamics of the concentration and 15N enrichment of the major amino acids in xylem sap were determined concurrently. Sap flow velocity was also measured for sample trees. A new approach coupling amino acid concentrations to sap flow velocity for quantifying N remobilization was tested. A decrease of the labeled N contents of medium roots, tap roots, and trunk was observed concurrently to the increase in the labeled N content of new shoots. Remobilized N represented from previous year storage 54% of N recovered in new shoots. Arginine, citruline, γ-amino butyric acid, glutamic acid, and aspartic acid always represented around 80% of total amino acid and amide N in xylem sap and exhibited specific seasonal trends and significant diurnal trends. N translocation was mainly insured by arginine during the first 15 d after bud burst, and then by glutamic acid and citruline. The pattern of N remobilization estimated by the new approach was consistent with that measured by the classical labeling technique. Implications for quantifying N remobilization for large, field-growing trees are discussed.